Biocompatibilidade in vivo de membranas nanoestruturadas de Quitosana/Peo - Vulcani, V. A.S.; Franzo, V. S.; Rabelo, R. E.; Rabbers, A. S.; Assis, B. M.; D'ávila, M. A.; Antoni, S. M.B. [UNESP] (FapUNIFESP (SciELO), 2015)
Electrospinning is a technique that allows the preparation of nanofibers from various materials. Chitosan is a natural and abundant easily obtained polymer, which, in addition to those features, proved to be biocompatible. This work used nanostructured chitosan and polyoxyethylene membranes as subcutaneous implants in Wistar rats to evaluate the biocompatibility of the material. Samples of the material and tissues adjacent to the implant were collected 7, 15, 30, 45 and 60 days post-implantation. Macroscopic integration of the material to the tissues was observed in the samples and slides for histopathological examination that were prepared. It was noticed that the material does not stimulate the formation of adherences to the surrounding tissues and that there is initial predominance of neutrophilia and lymphocytosis, with a declining trend according to the increase of time, featuring a non-persistent acute inflammatory process. However, the material showed fast degradation, impairing the macroscopic observation after fifteen days of implantation. It was concluded that the material is biocompatible and that new studies should be conducted, modifying the time of degradation by changes in obtaining methods and verifying the biocompatibility in specific tissues for biomedical applications.
Keywords: Biomaterials; Electrospinning; Nanotechnology